2006
DOI: 10.1007/s10336-005-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations

Abstract: At St Kilda, Outer Hebrides, a large colony of great skuas Stercorarius skua feed extensively on one of the largest colonies of Leach's storm-petrels Oceanodroma leucorhoa in Europe, but little is known about the dynamics of this predator-prey system. Recently published population estimates of storm-petrels make it possible to estimate the impact of skua predation for the first time. Although skuas in the southern hemisphere catch petrels attending breeding colonies at night, it is not known whether congeners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…Priddel and Carlile, 1995;Votier et al, 2006). Moreover, many species disperse to other islands to breed, suggesting that developing or retaining a memory for the scent of the home burrow or colony would not be required for homing in pre-reproductive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Priddel and Carlile, 1995;Votier et al, 2006). Moreover, many species disperse to other islands to breed, suggesting that developing or retaining a memory for the scent of the home burrow or colony would not be required for homing in pre-reproductive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This coincided with heavy predation of adult Storm-petrels by a large population of Great Skuas Stercorarius skua (Votier et al 2006), estimated to consume approximately 15 000 adults each year (Phillips et al 1999). It is unclear whether this level of predation will continue but declines in alternative food sources may lead to increased reliance on seabirds as prey (Votier et al 2004).…”
mentioning
confidence: 99%
“…Therefore, our findings most likely represent predation or scavenging and as the only predatory terrestrial mammal on Hirta, this is almost certainly by field mice. Skuas are known predators of adult Storm-petrels on St Kilda (Phillips et al 1999, Votier et al 2006) and although corvids have been observed excavating Stormpetrel burrows (Huntingdon et al 1996), such behaviour American Crow (C.brachyrhynchos) (?) * n (for fledging success in years 1991-1993) = 160; BP -breeding pairs; AOS -apparently occupied sites, (?)…”
mentioning
confidence: 99%
“…However, if the predator is only a facultative predator and an opportunistic feeder and scavenger, doubts can arise, especially because such predators are commonly abundant due to human activities and some of their prey can be endangered species (Oro et al 2009). Large seabirds such as gulls and skuas are facultative predator of long-lived smaller seabirds, many of them endangered (Oro et al 2005(Oro et al , 2009Stenhouse et al 2000;Votier et al 2006). Faced with this situation wildlife managers have to decide whether this interaction has to be allowed to occur (with or without modulation) or whether, on the contrary, needs to be extirpated or at least alleviated.…”
Section: Managing Predator-prey Interactionsmentioning
confidence: 96%